Mutations of p53 gene can be detected in the plasma of patients with large bowel carcinoma. Issue 8 (August 1998) - Mayall, F; Jacobson, G; Wilkins, R; Chang, B
Abstract : AIMS: To attempt to detect p53 gene mutations in the plasma of patients with large bowel carcinoma. METHODS: Plasma was collected from 20 control patients with no history of cancer and from 17 patients with large bowel carcinoma. Corresponding tumour and benign lymph node (control) samples for each of the carcinoma patients were obtained from paraffin blocks. A Dukes' stage was determined for each tumour. DNA was extracted from the plasma samples and the paraffin embedded tissue using previously described methods. A nested primer polymerase chain reaction protocol was used for the amplification of exons 5 to 8 of the p53 gene. "Cold" single strand conformational polymorphism (SSCP) was performed on mini gels and silver stained. Abnormal bands were excised, the DNA eluted, and reamplified for automated dye termination sequencing. Any sample showing an apparent mutation was rechecked from the original extracted DNA sample at least three times. RESULTS: p53 gene mutations were not found in the control specimens. They were found in both the primary tumour and the plasma in three cases, in the primary tumour alone in one case, and in the plasma alone in two cases. One of the latter two cases also had metastatic transitional cell carcinoma of the bladder and the other had widespread metastatic deposits. One of the cases with mutant DNA in both the plasma and the primary was a Dukes' stage B tumour. The others were Dukes' C and Dukes' D. CONCLUSIONS: p53 gene mutations can be detected in the plasma of some patients with large bowel carcinoma and these are concordant with those in the primary carcinomas.